2007
DOI: 10.1590/s0036-46652007000500010
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of antibodies against Leptospira spp. in horses of the urban area of Londrina, Paraná, Brazil

Abstract: SUMMARYA total of 320 horses were studied in this paper, both male and female, between two and 17 years of age, which were used for traction of wagons in the urban area of the municipality of Londrina (PR). These animals were kept, after their daily work, in abandoned areas or plots, in the outskirts of the urban area of the city. When these animals were attended by the veterinarians, between 1996 and 2005, none of them presented symptoms suggesting leptospirosis. The most frequent reasons for the visit were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
27
1
12

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 11 publications
8
27
1
12
Order By: Relevance
“…1999); (Faber et al 2000); (Donahue and Williams. 2000) Grippotyphosa, Icterohaemorrhagiae Europe (Donahue et al 1995); (Dwyer et al 1995); (Wollanke et al 2001) Bratislava, Icterohaemorrhagiae, Sejroe Sweden (Baverud et al 2009) Bratislava Mongolia (Odontsetseg et al 2005) Icterohaemorrhagiae, Copenhageni, Bratislava Brazil (Hashimoto et al 2007); (Braga et al 2011); (Coiro et al 2012); (Hamond et al 2012); (Pinna et al 2012); (Hamond et al 2013); (Pinna et al 2014) Icterohaemorrhagiae, Bratislava, Pomona Italy (Ebani et al 2012) Sejroe, Bratislava Korea (Jung et al 2010) Copenhageni, Bratislava Netherlands (Houwers et al 2011) Bratislava, Pomona Icterohaemorrhagiae Croatia Grippotyphosa, Sejroe Nothern Poland (Arent and KedzierskaMieszkowska. 2013) Copenhageni South-eastern Australia (Dickeson and Love.…”
Section: Common Serovars Affecting Horses and Their Geographical Locamentioning
confidence: 99%
“…1999); (Faber et al 2000); (Donahue and Williams. 2000) Grippotyphosa, Icterohaemorrhagiae Europe (Donahue et al 1995); (Dwyer et al 1995); (Wollanke et al 2001) Bratislava, Icterohaemorrhagiae, Sejroe Sweden (Baverud et al 2009) Bratislava Mongolia (Odontsetseg et al 2005) Icterohaemorrhagiae, Copenhageni, Bratislava Brazil (Hashimoto et al 2007); (Braga et al 2011); (Coiro et al 2012); (Hamond et al 2012); (Pinna et al 2012); (Hamond et al 2013); (Pinna et al 2014) Icterohaemorrhagiae, Bratislava, Pomona Italy (Ebani et al 2012) Sejroe, Bratislava Korea (Jung et al 2010) Copenhageni, Bratislava Netherlands (Houwers et al 2011) Bratislava, Pomona Icterohaemorrhagiae Croatia Grippotyphosa, Sejroe Nothern Poland (Arent and KedzierskaMieszkowska. 2013) Copenhageni South-eastern Australia (Dickeson and Love.…”
Section: Common Serovars Affecting Horses and Their Geographical Locamentioning
confidence: 99%
“…Nevertheless, this serovar is uncommon and we only found one case, while Linhares et al (2005), who studied the prevalence of serovars of Leptospira interrogans in 182 serum samples from horses of the Goiânia micro-region using the MAT method, did not find any positive results for this serovar. The fact that the Icterohaemorrhagiae serovar was also only identified on a single property in the present study is more controversial, as this serovar has been found in many studies and is regarded as one of the most prevalent ones in the country (Langoni et al, 2004;Gomes et al, 2007;Hashimoto et al, 2007;Jorge et al, 2011;Coiro et al, 2012). The findings with respect to Grippotyphosa may indicate a specific enzootic area for this serovar in the Bananeiras and Borborema counties.…”
Section: Discussionmentioning
confidence: 45%
“…The most frequent serovar was Icterohaemorrhagiae. Hashimoto et al (2007) studied 320 equines that were used to pull wagons in Londrina, Paraná, between 1996 and 2005, using MAT to investigate 22 serovars, and obtained positive results from 66.88%. Icterohaemorrhagiae was the most likely serovar.…”
Section: Discussionmentioning
confidence: 99%
“…seem to be the main risk factors for infection (ROBERTS, 1969;FAINE, 1982;HASHIMOTO et al, 2007). Kouam et al (2010) studied serum from 773 equines in four regions of Greece, using ELISA to investigate the presence of anti-IgG for Toxoplasma, Leishmania, Echinococcus and Trichinella.…”
Section: Discussionmentioning
confidence: 99%